Improving Mechanical Properties of Thermoset Biocomposites by Fiber Coating or Organic Oil Addition - Truc T. Ngo; James G. Kohl; Tawni Paradise; Autumn Khalily; Duane L. Simonson (International Journal of Polymer Science)
Two different thermoset biocomposite systems are experimented in this study with the hope to improve their mechanical properties. Fiberglass and hemp, in form of fabrics, are used to reinforce the thermoset polymer matrix, which includes a traditional epoxy resin and a linseed oil-based bioresin (UVL). The fiber/polymer matrix interface is modified using two different approaches: adding a plant-based oil (pine or linseed) to the polymer matrix or coating the fibers with 3-(aminopropyl)triethoxysilane (APTES) prior to integrating them into the polymer matrix. Epoxy resin is cured using an amine-based initiator, whereas UVL resin is cured under ultraviolet light. Results show that hemp fibers with APTES prime coat used in either epoxy or UVL matrix exhibit some potential improvements in the composite’s mechanical properties including tensile strength, modulus of elasticity, and ductility. It is also found that adding oil to the epoxy matrix reinforced with fiberglass mostly improves the material’s modulus of elasticity while maintaining its tensile strength and ductility. However, adding oil to the epoxy matrix reinforced with hemp doubles the material’s ductility while slightly reducing its tensile strength and modulus of elasticity.